Massive blood clot following traumatic tracheal intubation: misdiagnosis using the C‐MAC® Flexible Intubation Video Endoscope. Issue 1 (2nd April 2014) - Tay, Stanley; Magness, Andrew; Hicks, Chelsea; Blum, Philip; Jolley, Daniel; Spain, Brian
Summary: Video laryngoscopy and bronchoscopy in anaesthesia is commonly used both to improve visualisation of the airway and as an educational tool. We describe a patient undergoing laparoscopic insertion of a peritoneal dialysis catheter, who suffered almost complete airway obstruction from a massive blood clot following traumatic tracheal intubation using a bougie. Using the C‐MAC® Flexible Intubation Video Endoscope a misdiagnosis was made that delayed appropriate management. Successful removal of the blood clot was achieved through suspension laryngoscopy and the patient made a full recovery. This case highlights the problems of using the C‐MAC® Flexible Intubation Video Endoscope as a diagnostic tool. A laboratory comparison with the Olympus video bronchoscope is also described.